Research on cloud storage systems supporting secure sharing - Yan SONG; Zhen HAN; Jian-jun LI; Lei HAN (Tongxin xuebao)
A practical scheme for the cloud storage system was proposed to ensure security and efficiency during data sharing.The scheme which combine attribute-based encryption,proxy encryption with symmetric encryption,could integrate access control,efficient search with encryption well together.The scheme archived conjunctive-keyword non-field subset search by using bilinear mapping and polynomial equation.The scheme reduced the cost of decryption by outsourcing most of the decryption operations from the terminal to the cloud.At last,the performance was analyzed and an experiment was made for verification.